User's perceptions of physical elements in the hospital school environment - Mat So’od, Noor Fatehah; Abdullah, Fadzidah (IIUM, 2013)
The notion of providing special education services to hospitalized children is relatively new in Malaysia. During recovery process in any medical centre, children‟s education should not be overlooked as the children still need learning activities to maintain a sense of normality. The objective of this paper is to identify the factors of healing provided by physical elements in hospitals, and users‟ perception of learning environment in selected hospital schools. In order to evaluate the physical elementsand users‟ perception level, methods of observation and survey were adopted. Photos were documented as supplementary evidence of observation, which were later analysed. There were 51 respondents (n = 51) participated in the survey, whose roles were workers and users of the involved hospitals. Three (3) hospital schools were chosen as the units of analysis. They are hospital schools in Institute Paediatric Hospital Kuala Lumpur; in Hospital Ampang; and in Hospital Serdang. The result showed different satisfaction level among those three hospitals, in relation to users‟ preferences towards learning in hospital school environment. The identified physical elements contribute to healing and learning environment in hospital schools are in the range of average to medium high score 3.00-4.00, out of 5.00. All the three hospital schools need improvement on their physical elements, so that benefit of learning in hospital setting can be maximized